A Novel beta-Glucosidase from Sporidiobolus pararoseus: Characterization and Application in Winemaking - Baffi, Milla Alves [UNESP]; Tobal, Thaise [UNESP]; Lago, Joao Henrique G.; Leite, Rodrigo S. R.; Boscolo, Mauricio [UNESP]; Gomes, Eleni [UNESP]; Da-Silva, Roberto [UNESP] (Wiley-Blackwell, 2011)
For the first time, the production of an extracellular beta-glucosidase (Sp-beta-gl) by a Sporidiobolus pararoseus yeast strain is reported. The Sp-beta-gl activity was quantified, characterized, and assessed for its efficiency in releasing aroma-enhancing compounds in wines. The maximum enzymatic synthesis was after 72 h of growth in a complex media with 20 g/L of cellobiose. The optimal pH and temperature were 5.5 and at 50 degrees C, respectively. It showed a wide range of pH stability and exhibited quite high thermostability at low temperatures. In addition, this beta-glucosidase revealed tolerance to wine-associated inhibitory compounds (sugars and ethanol), showing suitable characteristics for all the stages of alcoholic fermentation. The hydrolysis of the glycosidic terpenes by Sp-beta-gl was studied by gas chromatography, and its ability to efficiently release free terpenols has been demonstrated. The concentrations of geraniol, linalool, alpha-terpineol, and nerol were significantly increased in treated wines. These results suggest the potential application of this new yeast beta-glucosidase as an aroma-enhancing enzyme in winemaking.
Keywords: Aroma; Beta-glucosidase; Sporidiobolus pararoseus; wine; Yeast